Influence of genetic background of engineered xylose-fermenting industrial Saccharomyces cerevisiae strains for ethanol production from lignocellulosic hydrolysates. (1st November 2017) - Lopes, Daiane Dias; Rosa, Carlos Augusto; Hector, Ronald E; Dien, Bruce S; Mertens, Jeffrey A; Ayub, Marco Antônio Záchia
Abstract: An industrial ethanol-producing Saccharomyces cerevisiae strain with genes of fungal oxido-reductive pathway needed for xylose fermentation integrated into its genome (YRH1415) was used to obtain haploids and diploid isogenic strains. The isogenic strains were more effective in metabolizing xylose than YRH1415 strain and able to co-ferment glucose and xylose in the presence of high concentrations of inhibitors resulting from the hydrolysis of lignocellulosic biomass (switchgrass). The rate of xylose consumption did not appear to be affected by the ploidy of strains or the presence of two copies of the xylose fermentation genes but by heterozygosity of alleles for xylose metabolism in YRH1415. Furthermore, inhibitor tolerance was influenced by the heterozygous genome of the industrial strain, which also showed a marked influenced on tolerance to increasing concentrations of toxic compounds, such as furfural. In this work, selection of haploid derivatives was found to be a useful strategy to develop efficient xylose-fermenting industrial yeast strains.